PARASITIC HELMINTHS AND THEIR BIOCHEMICAL AND PHYSIOLOGICAL CHARACTERISTICS (Web of Teachers: Inderscience Research, 2024)
During evolutionary development, according to the morphological structure of the helminth's body, the father adapted to a parasitic lifestyle, especially to the anaerobic digestion of substances. The biochemical description of adaptation to life as an anaerobic organism is a feature of metabolism and energy in helminths. An increase in the activity of certain enzyme systems in adulthood, rapid growth, development and rapid provision of protein biosynthesis to leave numerous offspring are the main signs of adaptation of helminths to parasitic life.